Political Communication Education for Beginner Voters in Convenient Regional Head Elections in 2024 - Kamil, Indriyati; Indah, Diani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The Election Supervisory Body (Bawaslu) of Subang Regency plays an important role in carrying out the function of political communication education for novice voters. This study aims to find out the strategy carried out by Bawaslu in political communication education, as well as communication barriers in conveying political messages at the 2024 Simultaneous Regional Elections. This study uses a qualitative research method with a qualitative descriptive research approach. The data was collected through in-depth interviews, literature studies, and observation. The research results show that the Political Communication Education Strategy for beginner voters in the 2024 Simultaneous Regional Elections begins with Establishing a Participatory Supervisory Cadre School (SKPP) to facilitate information flow and optimize information. Using social media platforms such as Instagram and websites, carrying out outreach activities through the